2020
DOI: 10.3390/cancers12071775
|View full text |Cite
|
Sign up to set email alerts
|

Comment on McCarthy, C.; et al. Developing Picornaviruses for Cancer Therapy. Cancers 2019, 11, 685

Abstract: I would like to make the following corrections to the publication by McCarthy et al [...]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 6 publications
(14 reference statements)
0
0
0
Order By: Relevance
“…Studies have shown that PDGF-BB is a potent mitogen and chemoattractant of PASMC. This significant growth factor causes PASMC proliferation and Migration, and participates in vascular remodeling in the development of pulmonary arterial hypertension [12][13][14] in small pulmonary arteries of PAH patients is higher than that of non-PAH patients [15][16]. Likewise, the PDGF signaling pathway has also been shown to be involved in pulmonary vascular remodeling [17].…”
Section: The Relationship Between Pdgf-bb and Pulmonary Hypertensionmentioning
confidence: 99%
“…Studies have shown that PDGF-BB is a potent mitogen and chemoattractant of PASMC. This significant growth factor causes PASMC proliferation and Migration, and participates in vascular remodeling in the development of pulmonary arterial hypertension [12][13][14] in small pulmonary arteries of PAH patients is higher than that of non-PAH patients [15][16]. Likewise, the PDGF signaling pathway has also been shown to be involved in pulmonary vascular remodeling [17].…”
Section: The Relationship Between Pdgf-bb and Pulmonary Hypertensionmentioning
confidence: 99%